Wifi positioning system / Amalina Abdul Halim - Abdul Halim, Amalina (Faculty of Information Technology and Quantitative Sciences, 2006)
In recent years, wireless technology with its sub standard 802.11 gaining popularityin deploying for positioning system. With development of mobile computing devices and wireless technique, location detection system is used to determine users location either in indoor or outdoor environment that relies on WiFi signal strength. The aim of this project is to develop an outdoor positioning system that can estimate the location of mobile devices based on signal strength that broadcast by access point. Beside that this project also apply prototype for UiTM bus application which is can determine the location of the bus and the arrival time of the bus at next bus stop. During data collection, empirical model method is used in order to construct the reference table. Using empirical model in case of wireless positioning system is basically compares the signal strength and find the closet match in the known entries in reference table. This paper present the experimental results that demonstrate the ability of Wifi Positioning system to estimate location of the devices using K-NN algorithm and result in application part is shown based on highest percentage accuracy of time taken to intend bus stop.